The development of medical law in Malaysia: the past, present and future challenges - Jahn Kassim, Puteri Nemie (2017)
The Malaysian Medical Law landscape has changed considerably over the past ten years due to increasing legislative and judicial intervention in fundamental issues affecting a person’s health and well-being. As the frontiers of medical knowledge and technology are continually expanding, the performance of medical professionals is constantly put under scrutiny. Medical professionals are no longer accorded unparalleled level of deference but instead, are expected to display a greater sense of accountability in all aspects of their actions. While medical paternalism has been thrusted into the backseat, the concept of patient autonomy has emerged to become the dominant ethos in the development of medical law. Patients nowadays have become much more aggressive in asserting their rights and this has subsequently caused the development of medical law to become much more prominent. Medical law is a challenging legal area as it draws on a wide range of existing legal subjects including tort law, criminal law, family law and contract law. The intervention of law in various aspects of medical practice in Malaysia has profoundly altered the legal boundaries of what are considered acceptable conducts in issues relating to medical negligence, consent to medical treatment, organ transplant, abortion and euthanasia. Consequently, medical professionals need to be geared up to meet the demands of evolving legal standards. By constantly educating themselves with knowledge on the developments of the law relating to their practice would enable them to continuously provide infallible services and relentlessly sustain the ideals of professionalism.